Method for synthesizing p-aminophenyl-beta-hydroxyethyl sulfone through hydrogenation reduction by taking MOFs (Metal-Organic Frameworks) derived carbon material as catalyst
By using MOFs-derived carbon materials as catalysts, the problems of high cost of precious metal catalysts and easy deactivation of non-precious metal catalysts are solved, and the efficient hydrogenation reduction of p-aminophenyl-β-hydroxyethyl sulfone is achieved, with high conversion and selection It has good catalyst stability and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411335577.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
The existing precious metal catalysts have high cost, poor dehalogenation inhibition and non-selective hydrogenation in the hydroreduction method, and the reaction conditions of non-precious metal catalysts such as Rainy Nickel are harsh, prone to inactivation and dehydroxyl inhibition. Poor, limiting its industrial application.
The MOFs-derived carbon material is used as a catalyst to prepare Co and N doped materials by room temperature stirring and pyrolysis, which is used for the hydroreduction of p-nitrophenyl-β-hydroxyethyl sulfone, which improves catalytic activity and reduces costs.
The high conversion and selectivity of p-aminophenyl-β-hydroxyethyl sulfone is achieved, and the catalyst has good stability and reusability, solving the problems of deactivation and recycling of existing catalysts.
Smart Images

Figure CN119219530A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of non-noble metal catalytic hydrogenation, and in particular to a method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts. Background Art
[0002] p-Aminophenyl-β-hydroxyethyl sulfone is an important intermediate for preparing vinyl sulfone type reactive dyes, and is generally prepared by reducing p-nitrophenyl-β-hydroxyethyl sulfone. Common industrial reduction methods for nitro compounds include alkali sulfide reduction, catalytic hydrogenation reduction, iron powder reduction, hydrazine hydrate reduction, etc. In order to develop environmentally friendly processes and meet the requirements of green chemical production, catalytic hydrogenation reduction has become a common method for preparing aromatic amine compounds in the current industry.
[0003] Although the precious metal catalysts such as Pd and Pt used in the existing catalytic hydrogenation process have high catalytic activity, they have the problems of high production cost and poor dehalogenation inhibition. In addition, the highly active precious metals will even reduce the nitro group, carbonyl group and double bond at the same time, resulting in non-selective hydrogenation. These problems undoubtedly limit their application and drive researchers to develop more economical and green alternatives. Considering the economic cost and scarcity of precious metal atoms, the abundant resources of transition metal-based hydrogenation catalysts have attracted widespread attention from researchers. However, the non-precious metal catalysts such as Raney nickel used in the existing process have problems such as harsh reaction conditions, easy deactivation, low catalytic activity and poor dehalogenation inhibition. Chinese invention patent CN101362712A prepares a nickel-aluminum alloy catalyst for catalytic hydrogenation to prepare p-aminophenyl-β-hydroxyethyl sulfone, but its catalyst preparation process is complicated and the entire process flow is relatively cumbersome. The patent application with publication number CN108003073A prepared a modified skeleton nickel catalyst for catalytic hydrogenation to prepare p-aminophenyl-β-hydroxyethyl sulfone. The catalyst is easily deactivated during use and has poor catalyst stability. Chinese invention patent CN102336691A uses Raney nickel as a catalyst for nitro hydrogenation reduction. The catalyst has poor dehydroxylation inhibition and requires the addition of dehalogenation inhibitor ethanolamine during the reaction. In addition, the characteristic of Raney nickel's easy spontaneous combustion in the air also makes its recycling after the reaction challenging and risky. In view of the problems existing in the catalytic hydrogenation process reported above, from the perspectives of economic benefits and operability, none of them is the best choice for large-scale application. Summary of the invention
[0004] The object of the present invention is to provide a method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using a MOFs-derived carbon material as a catalyst. The catalyst preparation process used in the present invention is simple, and the introduction of Zn is conducive to improving the problem of Co nanoparticle agglomeration, and the use of a non-precious metal catalyst is conducive to reducing costs. The c-MOFs-derived carbon material used in the present invention has richer and more uniform Co and N doping than Co / C and the material obtained by direct pyrolysis of ZIF-67, and exhibits excellent catalytic activity in the hydrogenation reaction of p-nitrophenyl-β-hydroxyethyl sulfone, and has the advantages of high yield and selectivity of the target product, reusability, and environmental friendliness, and has good application prospects.
[0005] The purpose of the present invention can be achieved through the following technical solutions.
[0006] A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts, comprising:
[0007] Into a high-pressure reactor, add p-nitrophenyl-β-hydroxyethyl sulfone, MOFs-derived carbon material and anhydrous methanol in sequence, introduce hydrogen, stir and heat to 80-120°C, react at a constant temperature for 2-10 hours, cool to room temperature, separate the catalyst from the reaction system by centrifugation, and obtain the product p-aminophenyl-β-hydroxyethyl sulfone.
[0008] Furthermore, the mass ratio of the raw material p-nitrophenyl-β-hydroxyethyl sulfone to the MOFs-derived carbon material catalyst is 1:(0.04-0.16).
[0009] Furthermore, the hydrogen pressure is 1-4Mpa; and the stirring rate is 600-1200rpm.
[0010] Furthermore, the mass ratio of the p-nitrophenyl-β-hydroxyethyl sulfone to anhydrous methanol is 1:(4-8).
[0011] The MOFs-derived carbon material is prepared by a room temperature stirring method and subsequent pyrolysis method.
[0012] Furthermore, the preparation method of the MOFs-derived carbon material comprises the following steps:
[0013] (1) adding cobalt nitrate hexahydrate and zinc nitrate hexahydrate to anhydrous methanol, dissolving them by ultrasonication, and obtaining a metal salt mixed solution; adding 2-methylimidazole to anhydrous methanol, dissolving them by ultrasonication, and obtaining an organic ligand solution;
[0014] (2) The two are mixed and stirred evenly, and the precipitate is taken out by centrifugation, washed, and dried to obtain BMZIFs crystal material.
[0015] (3) The prepared BMZIFs crystalline material is heated and calcined in an inert atmosphere to obtain a MOFs-derived carbon material.
[0016] The molar ratio of zinc nitrate hexahydrate to cobalt nitrate hexahydrate in step (1) is 2:1-1:3; the zinc ion concentration in the metal salt solution is 0.025-0.067 mol / L, and the cobalt ion concentration is 0.033-0.075 mol / L.
[0017] In the above method, in step (1), the concentration of the organic ligand solution is 0.4-0.6 mol / L.
[0018] In the above method, in step (2), the volume ratio of the metal salt mixed solution to the organic ligand solution is 1:1; the stirring time is 12-24 hours; and the drying temperature is 60-80°C.
[0019] In the above method, in step (3), the inert atmosphere is a nitrogen atmosphere; the calcination temperature is 700-1000°C, the calcination time is 2-3h, and the heating rate is 2-3°C / min.
[0020] Compared with the prior art, the technical effects of the present invention are as follows:
[0021] In the preparation method provided by the present invention, the introduction of Zn can prevent the aggregation of Co nanoparticles and promote uniform distribution to a certain extent, and can increase the porosity and specific surface area of the material after evaporation at high temperature, which is helpful to improve the catalytic reaction activity; secondly, the c-MOFs-derived carbon material involved in the present invention has high catalytic activity, the highest conversion rate of nitrophenyl-β-hydroxyethyl sulfone reaches 98.03%, and the selectivity of aminophenyl-β-hydroxyethyl sulfone reaches 96.68%. Under the same reaction conditions, compared with the MOFs-derived carbon materials obtained by calcining BMZIFs with four other different zinc-cobalt molar ratios and the f-MOFs-derived carbon materials obtained by calcining directly synthesized ZIF-67, it has higher catalytic activity. Moreover, the preparation method of the catalyst provided by the present invention is simple, the preparation cost is low, and the separation from the reaction system can be achieved by centrifugal operation. It has good recyclability and stability, effectively solves the problems of the difficulty in separating, recovering and reusing existing catalysts, and has good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the powder X-ray diffraction pattern of MOFs-derived carbon materials;
[0023] Figure 2Scanning electron microscope images of MOFs-derived carbon materials, where (a) is a-MOFs-derived carbon material, (b) is b-MOFs-derived carbon material, (c) is c-MOFs-derived carbon material, (d) is d-MOFs-derived carbon material, (e) is e-MOFs-derived carbon material, and (f) is f-MOFs-derived carbon material;
[0024] Figure 3 The effects of the MOFs-derived carbon materials prepared in Examples 1 to 5 on catalytic performance;
[0025] Figure 4 This is a performance test result diagram of the c-MOFs derived carbon material obtained in Example 3;
[0026] Figure 5 This is a transmission electron micrograph of the c-MOFs-derived carbon material obtained in Example 3;
[0027] Figure 6 This is a transmission electron micrograph of the f-MOFs-derived carbon material obtained in Example 6. DETAILED DESCRIPTION
[0028] The present invention is further described below by way of examples, but the patent rights are not limited to these examples.
[0029] Example 1
[0030] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 5.33mmol of zinc nitrate hexahydrate and 2.67mmol of cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e., a-BMZIFs crystal material. The prepared a-BMZIFs was heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the a-MOFs-derived carbon material.
[0031] Figure 1 This is the powder X-ray diffraction pattern (PXRD) of the a-MOFs-derived carbon material obtained in this example. In the figure, the a-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, corresponding to the characteristic peaks of single substance Co.
[0032] Figure 2a is a scanning electron microscope image (SEM) of the a-MOFs derived carbon material obtained in this example. It can be observed in the figure that the derivative material after pyrolysis retains the structure of its precursor rhombic dodecahedron to a certain extent compared with the parent template, but the particle size is slightly reduced, the crystal surface becomes rougher, a small amount of particles are loaded on the surface of the derivative material, and a very small amount of carbon nanotubes are also produced.
[0033] Example 2
[0034] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 4.8mmol of zinc nitrate hexahydrate and 3.2mmol of cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e., b-BMZIFs crystalline material. The prepared b-BMZIFs was heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the b-MOFs-derived carbon material.
[0035] Figure 1 This is the powder X-ray diffraction pattern (PXRD) of the b-MOFs-derived carbon material obtained in this example. In the figure, the b-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, which correspond to the characteristic peaks of single substance Co.
[0036] Figure 2 b is a scanning electron microscope (SEM) image of the b-MOFs derived carbon material obtained in this example. It can be observed in the figure that the derivative material after pyrolysis retains the structure of its precursor rhombic dodecahedron to a certain extent compared with the parent template, but the particle size is slightly reduced, the crystal surface becomes rougher, a small amount of particles are loaded on the surface of the derivative material, and a very small amount of carbon nanotubes are also produced.
[0037] Example 3
[0038] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 4mmol of zinc nitrate hexahydrate and 4mmol of cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e. c-BMZIFs crystalline material. The prepared c-BMZIFs was heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the c-MOFs-derived carbon material.
[0039] Figure 1 This is the powder X-ray diffraction pattern (PXRD) of the c-MOFs-derived carbon material obtained in this example. In the figure, the c-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, which correspond to the characteristic peaks of single substance Co.
[0040] Figure 2 c is a scanning electron microscope (SEM) image of the c-MOFs derived carbon material obtained in this example. It can be observed in the figure that the derived carbon material after pyrolysis retains the structure of its precursor rhombic dodecahedron to a certain extent compared with the parent template, and the crystal surface becomes rougher, a large number of small particles are loaded on the surface of the derived carbon material, and a small amount of carbon nanotubes are also produced.
[0041] Example 4
[0042] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 3.2mmol zinc nitrate hexahydrate and 4.8mmol cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e., d-BMZIFs crystal material. The prepared d-BMZIFs was heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the d-MOFs-derived carbon material.
[0043] Figure 1This is the powder X-ray diffraction pattern (PXRD) of the d-MOFs-derived carbon material obtained in this example. In the figure, the d-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, which correspond to the characteristic peaks of single substance Co.
[0044] Figure 2 d is a scanning electron microscope (SEM) image of the d-MOFs derived carbon material obtained in this example. It can be observed in the figure that the derived carbon material after pyrolysis retains the structure of the matrix well, the crystal surface becomes rougher, more small particles are loaded on the surface of the derived material, and a small amount of carbon nanotubes are also produced.
[0045] Example 5
[0046] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 2mmol zinc nitrate hexahydrate and 6mmol cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e., e-BMZIFs crystalline material. The prepared e-BMZIFs was heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the e-MOFs-derived carbon material.
[0047] Figure 1 This is the powder X-ray diffraction pattern (PXRD) of the e-MOFs-derived carbon material obtained in this example. In the figure, the e-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, corresponding to the characteristic peaks of single substance Co.
[0048] Figure 2 e is a scanning electron microscope (SEM) image of the e-MOFs derived carbon material obtained in this example. It can be observed in the figure that the derived carbon material after pyrolysis retains the parent structure well, but the particle size is slightly reduced, the crystal surface becomes rougher, more small particles are loaded on the surface of the derived carbon material, and a very small amount of carbon tubes are produced.
[0049] Example 6
[0050] In a 300mL beaker, add 0.048mol of 2-methylimidazole, then add 80mL of anhydrous methanol and ultrasonically dissolve to obtain an organic ligand solution; add 8mmol of cobalt nitrate hexahydrate to 80mL of anhydrous methanol, ultrasonically dissolve and mix evenly to obtain a metal salt mixed solution; slowly add the metal salt mixed solution to the 2-methylimidazole methanol solution while stirring it, continue stirring at room temperature for 24h after fully mixing, centrifuge to obtain the precipitate, wash, and dry at 80℃ for 24h to obtain the precursor of MOFs-derived carbon material, i.e., f-ZIFs crystal material. The prepared f-ZIFs were heated to 800℃ at a heating rate of 2℃ / min in a nitrogen atmosphere for calcination for 2h to obtain the f-MOFs-derived carbon material.
[0051] Figure 1 This is the powder X-ray diffraction pattern (PXRD) of the f-MOFs-derived carbon material obtained in this example. In the figure, the f-MOFs-derived carbon material exhibits three characteristic diffraction peaks at 44.2°, 51.5°, and 75.8°, which correspond to the characteristic peaks of single substance Co.
[0052] Figure 2 f is a scanning electron microscope (SEM) image of the f-MOFs derived carbon material obtained in this example. It can be observed in the image that the derived material after pyrolysis retains the structure of its precursor rhombic dodecahedron to a certain extent compared with the parent template, and the crystal surface becomes slightly rough.
[0053] Example 7
[0054] Effects of MOFs-derived carbon materials with different Zn / Co ratios on catalytic performance
[0055] The MOFs-derived carbon materials prepared in Examples 1 to 5 were used as reaction catalysts, and other reaction conditions were fixed. After the reaction was completed, the catalyst was separated by centrifugation, and the reaction solution was diluted and analyzed by high performance liquid chromatography. Figure 3 As shown, from Figure 3 It can be seen that c-MOFs-derived carbon materials have the best catalytic performance. In order to improve the reaction efficiency, c-MOFs-derived carbon materials are selected as catalysts.
[0056] Example 8
[0057] Performance test of MOFs-derived carbon materials for catalytic hydrogenation reduction to synthesize p-aminophenyl-β-hydroxyethyl sulfone
[0058] In a high-pressure reactor, 1.29 g of p-nitrophenyl-β-hydroxyethyl sulfone, 0.0772 g of c-MOFs-derived carbon material, and 10 mL of anhydrous methanol were added, and the reaction was carried out at a constant temperature of 100°C, a hydrogen pressure of 3 MPa, and a rotation speed of 1000 rpm for 6 hours. After the reaction, the c-MOFs-derived carbon material was separated by centrifugation, and the reaction solution was diluted and analyzed by high-performance liquid chromatography. The conversion rate of p-nitrophenyl-β-hydroxyethyl sulfone was 98.03%, and the selectivity of p-aminophenyl-β-hydroxyethyl sulfone was 96.68%.
[0059] Figure 4 The performance test result diagram of this embodiment is shown in FIG. Under given reaction conditions, as the reaction time increases, the conversion rate of the substrate gradually increases, and the conversion rate tends to be flat after 6 hours of reaction, while the yield of p-aminophenyl-β-hydroxyethyl sulfone begins to decrease slightly.
[0060] Example 9
[0061] Performance test of MOFs-derived carbon materials for catalytic hydrogenation reduction to synthesize p-aminophenyl-β-hydroxyethyl sulfone
[0062] In a high-pressure reactor, 1.29 g of p-nitrophenyl-β-hydroxyethyl sulfone, 0.061 g of f-MOFs-derived carbon material, and 10 mL of anhydrous methanol were added, and the reaction was carried out at a constant temperature of 100°C, a hydrogen pressure of 3 MPa, and a rotation speed of 1000 rpm for 6 hours. After the reaction, the f-MOFs-derived carbon material was separated by centrifugation, and the reaction solution was diluted and analyzed by high-performance liquid chromatography. The conversion rate of p-nitrophenyl-β-hydroxyethyl sulfone was 64.56%, and the selectivity of p-aminophenyl-β-hydroxyethyl sulfone was 78.13%.
[0063] Figure 5 and Figure 6 They are transmission electron microscope images of c-MOFs-derived carbon materials and f-MOFs-derived carbon materials, respectively. By comparison, it can be found that c-MOFs-derived carbon materials have smaller and more uniformly distributed Co nanoparticles, indicating that the spacing effect of Zn can prevent the aggregation of Co nanoparticles and promote uniform distribution. In addition, the catalytic performance of the c-MOFs-derived carbon material used in Example 8 is much higher than that of the f-MOFs-derived carbon material used in this embodiment, indicating that the catalytic activity of the synthesized bimetallic ZnCo-ZIF-derived material is higher than that of the monometallic ZIF-67-derived material. The doping of Zn not only improves the dispersibility and uniformity of Co nanoparticles, but also increases the porosity and specific surface area of the material after evaporation at high temperature, thereby exposing more active sites and increasing the mass transfer rate, thereby increasing the catalytic reaction activity.
[0064] The above embodiments of the invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts, characterized in that: Add p-nitrophenyl-β-hydroxyethyl sulfone, MOFs-derived carbon material and anhydrous methanol into a high-pressure reactor in sequence, introduce hydrogen, stir and heat to 80-120°C, react at a constant temperature for 2-10 hours, cool to room temperature, separate the MOFs-derived carbon material and the reaction liquid by centrifugation, and obtain the product p-aminophenyl-β-hydroxyethyl sulfone.
2. According to claim 1, a method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts, characterized in that: The mass ratio of the p-nitrophenyl-β-hydroxyethyl sulfone to the MOFs-derived carbon material catalyst is 1:(0.04-0.16).
3. According to claim 1, a method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts, characterized in that: The hydrogen pressure is 1-4Mpa; the stirring rate is 600-1200rpm.
4. The method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 1, characterized in that: The mass ratio of the p-nitrophenyl-β-hydroxyethyl sulfone to anhydrous methanol is 1:(4-8).
5. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 1, characterized in that The MOFs-derived carbon materials were prepared by room temperature stirring method and pyrolysis method.
6. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 5, characterized in that: The preparation of the catalyst specifically comprises the following steps: (1) adding cobalt nitrate hexahydrate and zinc nitrate hexahydrate to anhydrous methanol, dissolving them by ultrasonication, and fully mixing to obtain a metal salt mixed solution; adding 2-methylimidazole to anhydrous methanol, dissolving them by ultrasonication, and obtaining an organic ligand solution; (2) mixing the metal salt mixed solution described in step (1) with the organic ligand solution, stirring evenly, centrifuging to obtain a precipitate, washing, and drying to obtain a BMZIFs crystal material; (3) The BMZIFs crystalline material prepared in step (2) is heated and calcined in an inert atmosphere to obtain a MOFs-derived carbon material.
7. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 6, characterized in that: In step (1), the molar ratio of the zinc nitrate hexahydrate to the cobalt nitrate hexahydrate is 2:1 to 1:3; the zinc ion concentration in the metal salt solution is 0.025-0.067 mol / L, and the cobalt ion concentration is 0.033-0.075 mol / L.
8. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 6, characterized in that The concentration of the organic ligand solution in step (1) is 0.4-0.6 mol / L.
9. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 6, characterized in that In step (2), the volume ratio of the metal salt mixed solution to the organic ligand solution is 1:1; the stirring time is 12-24 hours; and the drying temperature is 60-80°C.
10. A method for synthesizing p-aminophenyl-β-hydroxyethyl sulfone by hydrogenation reduction using MOFs-derived carbon materials as catalysts according to claim 6, characterized in that The inert atmosphere in step (3) is nitrogen; the calcination temperature is 700-1000°C, the calcination time is 2-3h, and the heating rate is 2-3°C / min.
